2022
DOI: 10.9734/ajraf/2022/v8i4185
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Traditionally Used for the Treatment of Skin Diseases in Southern Punjab, Pakistan

Abstract: Skin conditions are among the most common health problems that affect people. Modern, allopathic, and natural medicine can all help to promote healthy skin.  Human skin problems can be successfully treated using medicinal herbs because they contain a wide variety of bioactive molecules. The goal of this research is to look into the dermatological properties of medicinal plants used by different ethnic communities in southern Punjab, Pakistan and it seeks to establish a foundation for the development of novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Leaves (n = 7) were the most commonly consumed, followed by young shoots, roots (n = 3 each), seeds, and fruits (n = 2 each). Azhar et al [34] reported the predominance of the leaves in traditional medicine from southern Punjab, Pakistan. Similar results were reported by Mir et al [35] from the Himalayan region of Kashmir.…”
Section: Gastronomic Usagementioning
confidence: 99%
“…Leaves (n = 7) were the most commonly consumed, followed by young shoots, roots (n = 3 each), seeds, and fruits (n = 2 each). Azhar et al [34] reported the predominance of the leaves in traditional medicine from southern Punjab, Pakistan. Similar results were reported by Mir et al [35] from the Himalayan region of Kashmir.…”
Section: Gastronomic Usagementioning
confidence: 99%
“…Nowadays medicinal species are being commercially used for many different extractions of various ingredients. Different herbs are used in the Ayurveda system of treatment and for the preparation of numerous homeopathic and modern allopathic drugs (Azhar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wild useful plants are disappearing near populated areas and this phenomenon is much more intense in developing countries with a rapid increase in population and expansion of residential and agricultural areas (Kala et al 2004;Hameed et al 2011;Azhar, 2014). The study area is not exempted from this situation.…”
Section: Introductionmentioning
confidence: 99%